A New Landscape of Multiple Dispersion Kinks in a High-T c Cuprate Superconductor - H. Anzai (Nature Portfolio, 2017)
Abstract Conventional superconductivity is caused by electron-phonon coupling. The discovery of high-temperature superconductors raised the question of whether such strong electron-phonon coupling is realized in cuprates. Strong coupling with some collective excitation mode has been indicated by a dispersion “kink”. However, there is intensive debate regarding whether the relevant coupling mode is a magnetic resonance mode or an oxygen buckling phonon mode. This ambiguity is a consequence of the energy of the main prominent kink. Here, we show a new landscape of dispersion kinks. We report that heavily overdoping a Bi2Sr2CaCu2O8+δ superconductor results in a decline of the conventional main kink and a rise of another sharp kink, along with substantial energy shifts of both. Notably, the latter kink can be ascribed only to an oxygen-breathing phonon. Hence, the multiple phonon branches provide a consistent account of our data set on the multiple kinks. Our results suggest that strong electron-phonon coupling and its dramatic change should be incorporated into or reconciled with scenarios for the evolution of high-T c superconductivity.